The Effect of Social Presence and Virtual Store Experience on Cunsumer Trust In Ciebon E-Commerce Platforms - Trinanda, Vega; Siska Ernawati Fatimah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study examines the influence of social presence and virtual store experiences on consumer trust in e-commerce platforms located in Cirebon City, delving into how affective and cognitive factors shape confidence in a localized online retail setting. Employing a quantitative approach with a causal associative design, data was collected through comprehensive questionnaires distributed to 385 individuals who had engaged in purchases on e-commerce sites, and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to test hypotheses and assess inter-variable relationships. The findings reveal that social presence has a positive and significant impact on consumer trust, while virtual store experiences similarly exert a positive and substantial effect. Collectively, these elements explain a considerable portion of the variance in trust, as indicated by a robust coefficient of determination, suggesting that trust emerges from a blend of emotional interactions and rational evaluations of system usability and virtual store features. Practically, the research provides valuable guidance for e-commerce managers to strengthen trust through improved social interactions and optimized virtual store designs, potentially increasing online purchases, supporting local digital businesses, and promoting sustainable economic progress and technological advancements in regional markets.